2019
DOI: 10.5603/imh.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vaccine for travellers — where are we now?

Abstract: The authors present a short summary of the current state of malaria vaccine development and the perspectives for the availability of a malaria vaccines for travellers from non-endemic countries. There is currently no commercially available malaria vaccine for travellers. The efficacy of the RTS,S/AS01 vaccine is limited and differs dramatically from the effects of other vaccines administered in travel medicine. In the current recommendations, the use of repellents is deemed the most important measure to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
(22 reference statements)
0
2
0
6
Order By: Relevance
“…Resistance has been reported to all anti-malarial drugs (22)(23)(24)(25)(26)(27). Several vaccine development studies on this issue have been performed, but few vaccines have demonstrated efficacy in Phase 2 studies (28)(29)(30)(31)(32)(33)(34)(35)(36). Activity was also poor, and there was a lack of consistent protection.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance has been reported to all anti-malarial drugs (22)(23)(24)(25)(26)(27). Several vaccine development studies on this issue have been performed, but few vaccines have demonstrated efficacy in Phase 2 studies (28)(29)(30)(31)(32)(33)(34)(35)(36). Activity was also poor, and there was a lack of consistent protection.…”
Section: Discussionmentioning
confidence: 99%
“…A fase eritrocítica é um momento crítico no ciclo biológico do parasita, as proteínas que participam deste evento são importantes candidatas para o desenvolvimento de uma vacina. Entre as proteínas merozoítas que possuem função biológica ligada à invasão dos reticulócitos/ eritrócitos estão: Antígeno 1 de Membrana Apical (AMA-1) e Proteína 1 da Superfície do Merozoíta (MSP-1) (COELHO et al, 2017;KUNA;GAJEWSKI, 2019).…”
Section: Mecanismos Fisiopatológicos Da Malária Como Alvos Para Vacinasunclassified
“…Com o desenvolvimento dessa vacina, busca-se uma ação biológica direta no alvo e, assim, prevenção parcial/ completa da infecção. Tais vacinas, se aplicadas em grande escala, poderiam interferir diretamente na epidemiologia da região, interrompendo o ciclo de transmissão do protozoário, independente do nível da endemicidade gerando uma interrupção no ciclo de transmissão do Plasmodium (COELHO et al, 2017;KUNA;GAJEWSKI, 2019).…”
Section: Avanços No Desenvolvimento De Vacinas Contra a Maláriaunclassified
See 1 more Smart Citation
“…Currently, no malaria vaccine is commercially available for travellers, and repellents are considered the most important measure to prevent infection. In high-risk destinations chemoprophylaxis is strongly advised (3)(4). Even though vector control (draining wetlands and use of insecticides to destroy mosquitoes) has successfully eradicated the disease in many countries, it remains a major problem in poor subtropical and tropical areas (2,(5)(6)(7).…”
mentioning
confidence: 99%